Case report: a fatal case of babesiosis in a splenectomized male patient from Western India - Godbole, Ravi; Gaur, Avantika; Nayar, Priyanka; Kiruthiga, Kala; D'Costa, Pradeep; Manchanda, Rumma; Khilari, Ajinkya; Shanmugam, Dhanasekaran; Muglikar, Kalpana D.; Kundu, Krishnendu (American Journal of Tropical Medicine and Hygiene, 2022)
Human babesiosis is a rare disease, caused by Babesia species and commonly transmitted by tick bite. Although human babesiosis is known to be asymptomatic in immunocompetent hosts, clinical cases of severe babesiosis have been reported from splenectomized or immunocompromised individuals. To our knowledge, only one case of human babesiosis in India has been previously reported. Here, we report a case of severe babesiosis with high parasitemia (similar to 70%) in a 30-year-old asplenic farmer. The patient presented with fever, yellowish discoloration of skin, oliguria, and anemia; he eventually developed multiorgan failure syndrome and died. Peripheral blood films were prepared and used to confirm the presence of piroplasms by microscopy. Total DNA isolated from blood was used for 18S ribosomal RNA gene fragment amplification by polymerase chain reaction, which was subjected to Sanger sequencing. Although 18S sequence indicated that the Babesia species infecting the patient was similar to that of other Babesia species originating from wild mammals, species identification could not be done. Phylogenetic analysis revealed that the patientderived pathogen is distinct because it forms a separate clade in the cladogram.